2021
DOI: 10.4067/s0718-50062021000200095
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de la responsabilidad social en estudiantes universitarios de educación

Abstract: El objetivo de este estudio es analizar el concepto de "responsabilidad social del estudiante universitario" adscrito al grado en educación infantil y primaria. Este término, tan necesario en la actualidad, atiende al valor "personal" de cada estudiante a partir de la formación universitaria para asumir su compromiso con la sociedad. La metodología empleada es cuantitativa (descriptivo-correlacional), llevándose a cabo la recogida de datos mediante el "cuestionario de responsabilidad social del universitario",… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
(20 reference statements)
0
3
0
10
Order By: Relevance
“…In this regard, Condori & Reyna (2019) found that 70% of university students consider that training with SR approach is adequate in their campus [5]. For Pegalajar et al, (2021), university academic training should contemplate aspects of social responsibility that allow the development of knowledge and attitudes in accordance with the social commitment that the future professional should assume with the natural environment [28]. In this line, Pérez et al, (2018) refers that in order to promote sustainable social development, there must be articulation between all areas of an institution which allows implementing projects under the mentioned approach [10].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Condori & Reyna (2019) found that 70% of university students consider that training with SR approach is adequate in their campus [5]. For Pegalajar et al, (2021), university academic training should contemplate aspects of social responsibility that allow the development of knowledge and attitudes in accordance with the social commitment that the future professional should assume with the natural environment [28]. In this line, Pérez et al, (2018) refers that in order to promote sustainable social development, there must be articulation between all areas of an institution which allows implementing projects under the mentioned approach [10].…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo, la responsabilidad social también está incorporada al contexto universitario, de esta manera aparece el concepto de Responsabilidad Social Universitaria (RSU), la cual es distinta a la Responsabilidad Social Empresarial (RSE), esta última engloba expectativas económicas, legales, éticas, así como sociales (Ormaza et al, 2020;Morales-Gualdrón et al, 2020;De Oliveira y Crisóstomo, 2021). Mientras que la RSU se centra en el impacto que tienen ciertas actividades de la organización en el desarrollo de la sociedad, bajo una perspectiva organizacional, social, educativa, cognitiva, como también ambiental (Rincón et al, 2017;Mendoza, Jaramillo y López, 2020;Pegalajar-Palomino et al, 2021;Mayor y Guillén-Gámez, 2021).…”
Section: Responsabilidad Social Universitaria: El Desafío De Las Univ...unclassified
“…También se indica que la RSU fortalece el compromiso cívico y la ciudadanía activa entre estudiantes universitarios y docentes a través del voluntariado, así como al proporcionar servicios sociales a la comunidad (Pegalajar-Palomino et al, 2021). El voluntariado universitario no busca algún tipo de compensación, sino que obtiene una herramienta de profundo cambio emocional y de mentalidad; entre los beneficios para los docentes, les otorga habilidades personales, como también sociales, gracias al aprendizaje de la experiencia vivencial, el cual puede estar asociado a actividades curriculares, así como extracurriculares y aun así resultar provechosas (Sarmiento-Peralta, Severino-Gonzáles y Santander-Ramírez, 2021).…”
Section: Responsabilidad Social Universitaria: El Desafío De Las Univ...unclassified
See 1 more Smart Citation
“…In higher education institutions, the teaching staff must adjust their pedagogical proposals based on the guidelines declared by the university [6]. Then, students would acquire skills that will allow them to behave professionally with a sense of social responsibility [7,8] It is considered that higher education must be of quality. However, this is a polysemic concept with different approaches to it.…”
Section: Introductionmentioning
confidence: 99%